Language Contact and Lexical Change: A Case Study of English Borrowings in The Igala Language - Ojochegbe, Ameh Timothy (Riviera Publishing, 2024)
This study examines the phenomenon of lexical borrowing from English into the Igala languages and its contribution to enriching vocabulary. Lexical borrowing is a linguistic phenomenon where one language adopts words from a donor language and incorporates them into the vocabulary of a receptor language. This usually occurs when speakers of one language encounter new concepts, technologies, or cultural elements from another language and import the corresponding words to express these concepts in their language. The research aim is to investigate how Igala speakers incorporate English words into their daily interactions as borrowed words. The study is a quantitative and qualitative descriptive analysis. A total of 30 respondents who are native speakers of the language from Dekina Local Government were interviewed and examined for their language use through observations. The analysis reveals that Igala speakers predominantly use their language. However, English lexical items that do not have their equivalent in the language were adapted phonologically and morphologically and incorporated into the language to fill lexical gaps.